State support for the development of eco-tourism in the international practice (Путеводитель предпринимателя)
Currently in the global tourism industry the development of rural tourism households is recognized ofthe highest priority for a modern economy. Theirformat is guest houses. State support for SME households is one of the most important conditions for their growth in the consumer market.